Seasonally flooded, and terra firme in northern Congo: Insights on their structure, diversity and biomass. (10th October 2018) - Ifo, Suspense Averti; Binsangou, Stoffenne; Ibocko Ngala, Lypsia; Madingou, Mady; Cuni‐Sanchez, Aida
Abstract: In the Congo basin, considerable uncertainty remains about the amount and spatial variation of carbon stocks. We studied two types of seasonally flooded forests (dominated by Guibourtia demeusei and Lophira alata ) and nearby terra firme forests in northern Congo. We sampled 1.25 ha per forest type and a total of 1, 400 trees ≥5 cm diameter. AGB ranged from 207–343 Mg/ha, with no significant differences between forest types. Few significant differences were observed in vegetation structure or tree diversity between forest types. Species richness and stem density of small trees were lower, and dominance was higher in Guibourtia plots, which are subject to greater flooding than Lophira plots. Guibourtia was absent from smaller diameter class in Guibourtia forests; and Uapaca spp. were more abundant in terra firme than in seasonally flooded plots. We show that both types of seasonally flooded forests store important quantities of AGB and should also be considered in forest conservation programmes. We recommend more research on seasonally flooded forests, on larger geographical extent, which assesses flood depth and duration, and measures tree height in the field, as we took a conservative approach to AGB estimates, and AGB could be even greater than we report here.